A novel P2Y(12) adenosine diphosphate receptor antagonist that inhibits platelet aggregation and thrombus formation in rat and dog models - Wang, Yi-Xin; Vincelette, Jon; da Cunha, Valdeci; Martin-McNulty, Baby; Mallari, Cornell; Fitch, Richard M; Alexander, Serene; Islam, Imadul; Buckman, Brad O; Yuan, Shendong; Post, Joseph M; Subramanyam, Babu; et al. (Thrombosis and haemostasis, 2007)
Irreversible platelet inhibitors, such as aspirin and clopidogrel, have limited anti-thrombotic efficacy in the clinic due to their bleeding risk. We have developed an orally active reversible P2Y(12) receptor antagonist, BX 667. The aim of this study was to determine if the reversible antagonist BX 667 had a greater therapeutic index than the irreversible P2Y(12) receptor antagonist clopidogrel. Since BX 667 is rapidly converted to its active metabolite BX 048 in rats, we first injected BX 048 intravenously (iv) in a rat arterial venous (A-V) shunt model of thrombosis. BX 048 dose- and concentration-dependently attenuated thrombosis. When administered orally, BX 667 and clopidogrel had similar efficacy, but BX 667 caused less bleeding than clopidogrel. In a rat model of a platelet-rich thrombus induced by vessel injury with FeCl(2), both BX 667 and clopidogrel exhibited higher levels of thrombus inhibition after oral administration compared to their potency in the A-V shunt model. Again, BX 667 caused less bleeding than clopidogrel. In a dog cyclic flow model, iv injection of either BX 667 or clopidogrel dose-dependently reduced thrombus formation with lower bleeding for BX 667 than clopidogrel. Inhibition of thrombosis was highly correlated with inhibition of ADP-induced platelet aggregation in these animal models. In dogs pre-treated with aspirin, BX 667 maintained its wider therapeutic index, measured by inhibition of platelet aggregation over bleeding, compared to the aspirin-clopidogrel combination. These data demonstrate that the reversible P2Y(12) receptor antagonist, BX 667, has a wider therapeutic index than clopidogrel in experimental models of thrombosis.